2018
DOI: 10.3389/fped.2018.00367
|View full text |Cite
|
Sign up to set email alerts
|

Referrals and Management Strategies for Pediatric Obesity—DocStyles Survey 2017

Abstract: Background: Childhood obesity care management options can be delivered in community-, clinic-, and hospital-settings. The referral practices of clinicians to these various settings have not previously been characterized beyond the local level. This study describes the management strategies and referral practices of clinicians caring for pediatric patients with obesity and associated clinician characteristics in a geographically diverse sample.Methods: This cross-sectional study used data from the DocStyles 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Our data also suggest that primary care physicians focused on the pediatric population perceive that a lack of adequate referral services for diet, physical activity, and weight management is a barrier to achieving successful obesity management. These perceptions align with the current literature that has reported limited geographic availability of obesity‐trained pediatrics physicians, as well as other concerns that come both with the lack of affiliation with teaching hospitals and with serving low‐income families (7,29‐31). A study focused on the American Board of Obesity Medicine found that only 38% of physicians who held this certification had a pediatric background (7), which is insufficient to meet the high demand of pediatric patients with overweight and obesity.…”
Section: Discussionsupporting
confidence: 78%
“…Our data also suggest that primary care physicians focused on the pediatric population perceive that a lack of adequate referral services for diet, physical activity, and weight management is a barrier to achieving successful obesity management. These perceptions align with the current literature that has reported limited geographic availability of obesity‐trained pediatrics physicians, as well as other concerns that come both with the lack of affiliation with teaching hospitals and with serving low‐income families (7,29‐31). A study focused on the American Board of Obesity Medicine found that only 38% of physicians who held this certification had a pediatric background (7), which is insufficient to meet the high demand of pediatric patients with overweight and obesity.…”
Section: Discussionsupporting
confidence: 78%
“…Reward options should not include snacks, sweetened beverages, or high-calorie foods; instead, outdoor sports or tours are recommended to promote physical activity. Management of childhood obesity is progressive and age-dependent, and it should be initiated as early as possible (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Reward options should not include snacks, sweetened beverages, or high calorie foods; instead, outdoor sports or tours are recommended to promote physical activity. Management of childhood obesity is progressive and age-dependent, and it should be initiated as early as possible (32,33). Based on the report of the Commission on Ending Childhood Obesity by the WHO in 2016, comprehensive programs that promote healthy school environments, health and nutrition literacy, and physical activity among school-age children and adolescents should be established and assisted by family-based, multicomponent lifestyle weight management services (34).…”
Section: Discussionmentioning
confidence: 99%